Da concepção do conceito de família como ideia de justiça no mundo contemporâneo - Pedro Tunes Aleixo (2022)
This is a research on the family institute in which it aims to verify whether the change in the conception of the concept of family impacts on the meaning of fundamental rights, and therefore, on the idea of contemporary justice that seeks to be based on the realization of fundamental rights under the ethics of Dr. Salgado's theory. To this end, it is necessary to make a historical – cultural – social perspective to elucidate the theme of the family institute over time, as well as to relate it to the philosophical and social theories indexed to the legal norms in force at the time and also the current ones that guard the rights of the family. The study comes from bibliographic and normative research on the points addressed. At the end of the reading, the reader will be given detailed reflection on the family institute and its impact on the meaning of fundamental rights.